Animal Models of Porphyria with Hepatic Involvement - Balogun, Oluwashanu; Nejak-Bowen, Kari (Seminars in Liver Disease, 2025)
The porphyrias are a group of metabolic disorders that are caused by defects in one of the eight enzymes that synthesize heme. A common feature of all porphyrias is accumulation of porphyrin precursors or porphyrins, which are intermediates of the heme biosynthesis pathway. Approximately 15% of heme biosynthesis occurs in the liver, and excessive hepatic production of porphyrin precursors caused by heme enzyme deficiencies can lead to neurovisceral manifestations. Additionally, in erythropoietic protoporphyria, porphyrins accumulate in the liver, leading to hepatic injury. These rare diseases have few effective medical therapies, and disease mechanisms are not always well understood. Animal models have provided a platform to study the pathophysiology of disease and test emerging therapies. In this review, the last of a three-part series, we describe the animal models that have been generated to study porphyrias with hepatic involvement. For each model, we discuss mechanisms of injury, phenotypic features, and the similarities and contrasts to human porphyria. We also describe preclinical studies that have utilized the model for therapeutic interventions. Overall, animal-based studies have made significant contributions to our understanding of porphyria and may lead to innovative therapies in the future.
Keywords: acute intermittent porphyria; variegate porphyria; hereditary coproporphyria; porphyria cutanea tarda; erythropoietic porphyria